Evaluación del ruido ambiental ocasionado por el parque automotor en cuatro planteles educativos de la ciudad de Tena, mediante la identificación de los niveles de presión sonora, para proponer un plan de manejo ambiental - Arévalo Zhagui, Carmen Valeria (2016)
This research reflects a thorough evaluation of the existing ambient noise in the study area, ie was based on the monitoring of existing levels of sound pressure in four educational establishments of the city of Tena, also in the preparation of an Environmental Management Plan control and noise mitigation. The methodology and criteria used in the evaluation were taken from existing legislation, Annex V of the Ministerial Agreement No 061 proposed by the Ministry of Environment of Ecuador. In order to comply with the objectives and achieve represent the existing ambient noise, a methodology according to the orientation of applied research. an environmental basis of the evaluated area line, the characteristics of educational plantes rose, points acoustic monitoring were identified and surveys were administered to students in each of the educational institutions in order to know the perception and the degree of acoustic annoyance over them. Measurements were performed two times daily for a week from 06h45 to 07H30 and 12H30 to 13H15 from. With the help of a EXTECH Sonometer were raised levels sound of each point pressure, the same which were compared with the maximum permissible ambient noise levels for such areas being 55dB, according to the Ministerial Agreement No. 061. In four educational establishments one LKeqPromedio for 66,30dB Point 1, Point 2 59,83dB, 67,01dB Point 3 and Point 4 of 63,24dB was obtained, obtaining a total average of the four educational establishments 64 10 dB in weighting A.